Cooking Education Improves Cooking Confidence and Dietary Habits in Veterans. Issue 4 (August 2019) - Dexter, Ashley S.; Pope, Janet F.; Erickson, Dawn; Fontenot, Catherine; Ollendike, Elizabeth; Walker, Emily
Purpose: The purpose of the study was to evaluate a 12-week cooking education class on cooking confidence, dietary habits, weight status, and laboratory data among veterans with prediabetes and diabetes. Methods: The sample for this study included 75 veterans within the Overton Brooks Veteran Affairs Medical Center who completed the 12-week class in an in-person group setting in Shreveport, Louisiana, or via Clinical Video Telehealth (CVT) in Longview, Texas. Veterans were referred to the Healthy Teaching Kitchen by their primary care provider or primary care dietitian. Enrollment in the class was on a volunteer basis. The cooking and nutrition education classes included topics such as carbohydrate counting, safety and sanitation, meal planning, and creating budget-friendly recipes. Participants completed 2 questionnaires for assessment of healthy dietary habits and confidence related to cooking. Changes in body weight, lipid panel, and hemoglobin A1C were assessed. Differences in class settings were tested via independent samples t tests. Paired samples t tests were completed to compare changes in mean laboratory results, weight, and questionnaire responses. Results: Subjects lost a mean 2.91 ± 5.8 lbs ( P < .001). There was no significant difference in percent change in laboratory data and weight between subjects participating via CVT and subjects in the live class. Overall, there was significant improvement in the confidence questionnaire ratings and Healthy Habits Questionnaire responses. Conclusions: Cooking and nutrition education can increase cooking confidence and dietary quality. These results provide support for the need for further research on the long-term effects of nutrition cooking education and for the benefits of using CVT software to provide education to remote facilities.